Increased neuromuscular transmission instability and motor unit remodelling with diabetic neuropathy as assessed using novel near fibre motor unit potential parameters. Issue 4 (April 2015) - Allen, Matti D.; Stashuk, Daniel W.; Kimpinski, Kurt; Doherty, Timothy J.; Hourigan, Maddison L.; Rice, Charles L.
Highlights Novel near fibre (NF) motor unit potential (MUP) parameters are used to detect neuromuscular transmission instability and motor unit remodelling in patients with neuropathy. In both DPN patients and controls, more complex motor units had greater instability. NF MUP analysis can be performed concurrent with motor unit number estimates (MUNEs) to provide a detailed assessment of neuromuscular status in patients with neuropathy.